Let's chat - Paquete, Catarina M. (2022)
Funding Information: C.P acknowledges the funding from FCT– Fundação para a Ciência e a Tecnologia, I.P. (FCT), Project MOSTMICRO-ITQB with refs UIDB/04612/2020 and UIDP/04612/2020. M. A. R. has received funding from the European Research Council (ERC) under the European Union’s Horizon 2020 research and innovation programme (Grant agreement No. 864669 ). A.E.R is funded by the Novo Nordisk Foundation (Ascending Investigator grant no. NNF21OC0067353) and the Danish Research Council (DFF 1026-00159). S.P is a Serra Húnter Fellow (UdG-AG-575) and acknowledges the funding from the ICREA Academia award and the Spanish Ministry of Science and Innovation (RTI2018-098360-B-I00 and PLEC2021-007802). LEQUiA [2017-SGR-1552] and Ecoaqua [2017SGR- 548] have been recognized as consolidated research groups by the Catalan Government. C.P and S.P acknowledge support of CA19123 COST ACTION PHOENIX. Funding Information: C.P acknowledges the funding from FCT– Fundação para a Ciência e a Tecnologia, I.P. (FCT), Project MOSTMICRO-ITQB with refs UIDB/04612/2020 and UIDP/04612/2020. M. A. R. has received funding from the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (Grant agreement No. 864669). A.E.R is funded by the Novo Nordisk Foundation (Ascending Investigator grant no. NNF21OC0067353) and the Danish Research Council (DFF 1026-00159). S.P is a Serra Húnter Fellow (UdG-AG-575) and acknowledges the funding from the ICREA Academia award and the Spanish Ministry of Science and Innovation (RTI2018-098360-B-I00 and PLEC2021-007802). LEQUiA [2017-SGR-1552] and Ecoaqua [2017SGR- 548] have been recognized as consolidated research groups by the Catalan Government. C.P and S.P acknowledge support of CA19123 COST ACTION PHOENIX. Publisher Copyright: © 2022 The Author(s)